Efficient mesoporous SO42−/Zr-KIT-6 solid acid catalyst for green diesel production from esterification of oleic acid. (1st September 2017) - Gopinath, S.; Kumar, P. Sahaya Murphin; Arafath, K.A. Yasar; Thiruvengadaravi, K.V.; Sivanesan, S.; Baskaralingam, P.
Graphical abstract: Esterification of oleic acid by Sulphated Zr-KIT-6 (20). Highlights: Hydrothermal synthesis and characterization of mesoporous Sulphated Zr-KIT-6 (SZK) solid acid catalyst. Biodiesel produced from oleic acid and jatropha oil with the conversion of 96% and 85% at 120 °C. The conformational mechanism for esterification and transesterification proposed. SZK is an environmentally benign catalyst and cost effective. The produced green diesel meets standard petro-diesel properties and can be used as blend for commercial use. Abstract: Highly ordered mesoporous sulphated Zr-KIT-6(x) [x = Si/Zr] solid acid catalysts were successfully synthesized by hydrothermal method. Different weight fractions of zirconium were loaded into fixed gel in the acidic medium and then sulphated to get sulphated Zr-KIT-6(x) catalysts. X-ray diffraction (XRD), surface area analysis (Brunauer-Emmett-Teller equation) and microscopic techniques (SEM and TEM) results suggest the incorporation of Zr 4+ into the silica KIT-6 framework by isomorphous substitution between Zr 4+ and Si 4+ ions. Diffuse reflection spectroscopy (DRS-UV) results reveal that Zr atoms are highly dispersed in +4 oxidation state. During the experiments it was observed that sulphated Zr-KIT-6 (20) showed the highest catalytic conversion for esterification of oleic acid (96%) and transesterification of jatropha oil (85%) at an optimized reaction conditions of 120 °C, 20:1 methanol to reactant molar ratio, 4 wt% catalyst loading and 6 h reaction time. The ester yields of 95% and 80% obtained from oleic acid and jatropha oil respectively. The used catalysts could be recycled up to three cycles with significant activity and stability.